THE RENDITIONS PRODUCED BY THE INTERPRETERS IN SERMON INTERPRETING AT ROCK CHURCH DENPASAR BALI - Johnli Hervie Lumi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2019)
This paper explores the renditions produced by the interpreters in sermon interpreting at ROCK Church Denpasar Bali. It aims at finding out and investigating the categories and the motives of the renditions produced by the interpreters in the setting under investigated. The method adopted for this study is a descriptive qualitative approach. The data of this study is based on six transcribed audio-video recordings of interpreter-mediated sermons on Sunday services, involving six visiting preachers, congregation, and three interpreters. The sermons are preached in English and interpreted short-consecutively into Indonesian. The data were collected through observation method which was applied at once with the implementation of note-taking technique, and were analyzed using the qualitative method and comparative technique. As a theoretical framework, the taxonomy of renditions proposed by Wadensjö (1998) has been utilized. The result of the study shows that there were eight categories of rendition produced by the interpreters in sermon interpreting on Sunday services at ROCK church Denpasar Bali. The categories of rendition produced by the interpreters were close renditions, expanded renditions, reduced renditions, substituted renditions, summarized renditions, two-part renditions, non-renditions, and zero renditions.